A general approach to realizing perovskite nanocrystals with insulating metal sulfate shells. Issue 23 (28th May 2021) - Gao, Feng; Wu, Jianghua; Zhao, Yilin; Song, Tinglu; Deng, Zhengtao; Wang, Peng; Wang, Yonggang; Li, Hongbo
Abstract : Perovskite nanocrystals with an insulating metal sulfate shell are synthesized. These novel core/shell structured nanocrystals show highly reduced energy transfer in film and suppressed halide exchange in solution. Abstract : The strategy of constructing the core/shell structure is of great importance in emitting semiconductor nanocrystals. However, the coating on soft metal halide perovskite nanocrystals at the single particle level remains a challenge because of the low compatibility between perovskites and common wide-band-gap semiconductors, such as ZnS and CdS. In addition, using these semiconductors as the shell layer requires high reaction temperatures, which often lead to undesirable chemical transformation. Herein we report a general route to passivate the perovskite nanocrystals by insulating metal sulfate shells. The passivating shell is created around the as-synthesized CsPbBr3 perovskite nanocrystals by initiating the reaction between an organic ammonium sulfate and a variety of metal ions in the presence of ligands. This new method allowed for creating insulating metal sulfate shells with controllable thicknesses and without unwanted chemical transformation. Importantly, these novel core/shell-structured nanocrystals show photoluminescence quantum yields near unity, highly suppressed energy transfer in film and suppressed halide exchange in solution.